CYTOGENETIC STIDY OF 366 AFFECTED CHILDREN WITH DOWN'S SYNDROME IN IRAN - D.D Farhud; H. Sadighi; H. Ameli; A. Bagheri; Z. Hosseini Mazhari (Tehran University of Medical Sciences, 1996)
Down's syndrome, or 21 trisomy, is the most common autosomal abnormality, with incidence of 1 per 815 live births in Iran. Worldwide reports indicate that about 95% are regular trisomy, or nondisjunction, 1% are mosaic and 4% due to translocation. However, these values show a geographical variation. A cytogenetic study of Down's syndrome, or trismoy 21, was carried out on 366 cases (202 males and 164 females) during a 10 year period (1974-1983) in Akbarabadi maternity hospital in Tehran. The lymphocyte chromosomes were stained with G-banding technique. Free trisomy 21 constituted 93.44%, D/G translocation 3.55% and G/G translocation 3.01%. Reciprocal translocation and mosaic were not observed. The values are compared with other studies in some of the countries of the countries of the region.